Acarbose monotherapy and weight loss in Eastern and Western populations with hyperglycaemia: an ethnicity‐specific meta‐analysis. Issue 11 (23rd May 2014) - Li, Y.; Tong, Y.; Zhang, Y.; Huang, L.; Wu, T.; Tong, N.
Summary: Objective: To demonstrate if weight loss achieved with acarbose in individuals with hyperglycaemia differs between Eastern and Western populations. Methods: Databases and reference lists of clinical trials on acarbose were searched. Eligible studies were randomised controlled trials of acarbose monotherapy in populations with hyperglycaemia of more than 12‐week duration that provided data on body weight (BW) or body mass index (BMI). Results: A total of 34 trials (6082 participants) were included. The effect of acarbose on BW was superior to that of placebo [weighted mean difference (WMD) = −0.52, 95% confidence interval (CI) −0.78 to −0.25], nateglinide (WMD = −1.33, 95% CI −1.51 to −0.75) and metformin (WMD = −0.67, 95% CI −1.14 to −0.20). Compared with placebo, there was a significantly greater weight loss of 0.92 kg (p < 0.05, I 2  = 88.8%) with acarbose in Eastern populations (WMD = −1.20, 95% CI −1.51 to −0.75) than that in Western populations (WMD = −0.28, 95% CI −0.59 to 0.03). Across all studies, the acarbose group achieved a significantly larger absolute weight loss of (change from baseline) 1.35 kg (p < 0.05, I 2  = 94.3%) in Eastern populations (WMD = −2.26, 95% CI −2.70 to −1.81) than in Western populations (WMD = −0.91, 95% CI −1.36 to −0.47). Nevertheless, the possible risk of bias in Eastern studies may influence the results. Conclusion: The effect of acarbose on weight loss seems to be more pronounced in Eastern than in Western populations with hyperglycaemia, and is superior to that of placebo, nateglinide and metformin across both ethnicities.